1995
DOI: 10.1055/s-2006-958032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Lignan-Enriched Fructus Schisandrae Extract on Hepatic Glutathione Status in Rats: Protection against Carbon Tetrachloride Toxicity

Abstract: The effect of a lignan-enriched extract of the fruits of Schisandra chinensis (FS) on hepatic glutathione (GSH) status was examined in both control and carbon tetrachloride (CCl4)-treated rats. FS treatment caused a dose-dependent enhancement in hepatic GSH status, as evidenced by significant increases in hepatic GSH level and activities of hepatic glucose-6-phosphate and glutathione reductase (GRD), as well as a decreased susceptibility of hepatic tissue homogenates to in vitro peroxide-induced GSH depletion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 2 publications
5
56
0
1
Order By: Relevance
“…With regard to hepatic protection, the lignans are correlated tightly with the increase in the hepatic levels of ascorbic acid, as well as the inhibition of NADPH oxidization and lipid peroxidation, which occur as the consequence of the induction effect of the hepatic cytochrome P-450 enzymatic system of the microsome. These lignans also protect against the cholestasis induced by toxic substances (27)(28)(29)(30). The aforementioned ligands contribute to the hepatic regeneration process via the induction of mRNA transcription for hepatocyte growth factor, as well as the stimulation of hepatocyte proliferation and increased blood flow to the liver.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to hepatic protection, the lignans are correlated tightly with the increase in the hepatic levels of ascorbic acid, as well as the inhibition of NADPH oxidization and lipid peroxidation, which occur as the consequence of the induction effect of the hepatic cytochrome P-450 enzymatic system of the microsome. These lignans also protect against the cholestasis induced by toxic substances (27)(28)(29)(30). The aforementioned ligands contribute to the hepatic regeneration process via the induction of mRNA transcription for hepatocyte growth factor, as well as the stimulation of hepatocyte proliferation and increased blood flow to the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in hepatic GSH level in Ixora treated rat could either be due to an effect on the de novo synthesis of GSH, its regeneration or both. As a consequence, hepatic GSH level could be sufficiently maintained to counteract the increased formation of free radicals as in the case of carbon tetrachloride toxicity 14 . The observed protective effect of the plant extract against carbon tetrachloride may be attributed to the presence of flavonoids, ascorbic acid, carotenoids, tannin and lignins among the plant constituents 16 .…”
Section: Graph 1: Liver Gsh Content In Different Groups Of Ratmentioning
confidence: 99%
“…This may result in significant damage to cell structures. Cumulatively, this is known as oxidative Studies also revealed that there are various herbal extracts induced oxidative stress by enhancing the decreased level of catalase (CAT), superoxidase dismutase (SOD), reduce glutathione (GSH) [10,11] and also Natural plant products have been widely used for medical purpose and according to Ayurveda, these medicine have less side effect when compared with allopathy medicine.In Ayurveda, plants are pose. Compare with allopathy medicine it have less side effects or no side effects.…”
Section: Introductionmentioning
confidence: 99%